2022
DOI: 10.3390/microorganisms10040726
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus salivarius CML352 Isolated from Chinese Local Breed Chicken Modulates the Gut Microbiota and Improves Intestinal Health and Egg Quality in Late-Phase Laying Hens

Abstract: Lactobacillus strains with fine probiotic properties are continuously needed in the laying hen industry to improve the animals’ gut health and production performance. In this study, we isolated 57 Lactobacillus strains from the gut microbiota of 17 different chicken breeds in China. We characterized the probiotic features of these isolates, and evaluated the effects of a selected strain, Lactobacillus salivarius CML352, on the production performance and gut health of the late-phase laying hens. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 88 publications
3
21
0
1
Order By: Relevance
“…Also, combined Bacillus strains caused an 8% improvement in laying performance compared to the control ( Yang et al, 2020 ). The increased egg production rate could be due to an improvement in nutrient utilization ( Souza et al, 2021 ), which is accrued to a positive effect of probiotics on the beneficial gut microbial population ( Xu et al, 2022 ) and gut morphology ( Song et al, 2019 ). In the current study, our findings revealed that Clostridium butyricum and Brevibacillus significantly improved egg production rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, combined Bacillus strains caused an 8% improvement in laying performance compared to the control ( Yang et al, 2020 ). The increased egg production rate could be due to an improvement in nutrient utilization ( Souza et al, 2021 ), which is accrued to a positive effect of probiotics on the beneficial gut microbial population ( Xu et al, 2022 ) and gut morphology ( Song et al, 2019 ). In the current study, our findings revealed that Clostridium butyricum and Brevibacillus significantly improved egg production rates.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, probiotics including Clostridium butyricum ( Xiang et al, 2019 ; Wang W. W. et al, 2020 ; Wang Y. et al, 2021 ), Bacillus sp. ( Neijat et al, 2019 ; Yang et al, 2020 ; Pan et al, 2022 ), and combined probiotics strains ( Ray et al, 2022 ; Xu et al, 2022 ) enhanced feed efficiency in laying hens. Similarly, in this study, Clostridium butyricum improved feed utilization, and consequently, the enhanced feed efficiency was a boost to the production potential of the animal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies have shown that L. salivarius can increase the body weight gain, body weight, and feed conversion ratio (FCR), while simultaneously reducing the contents of the total cholesterol, low-density lipoprotein, and triglyceride in the blood [ 10 , 11 , 12 , 13 , 14 ]. Lactobacillus salivarius displays high acid and bile salt tolerance and can facilitate its colonization by producing antimicrobial peptides and bacteriocin in the intestine, hence, adjusting the intestinal microflora and modulating the immune system [ 15 , 16 ]. Additionally, L. salivarius can reduce the organ damage caused by the infection of Mycoplasma gallisepticum (MG), Campylobacter , and Escherichia coli O78 , augmenting the immune responses after infectious bursal disease virus (IBDV) vaccination, enhancing the production of specific antibodies and stimulating lymphocyte proliferation [ 8 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%